Request Refusal Discourse in Japanese Female Interaction: An SFL Negotiation Analysis - Hayati, Novia (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
This study aims to investigate the discourse structure of refusal to requests in interactions among Japanese female university students, examining the roles adopted and assigned by speakers, the phases of refusal discourse, and the organization of moves. This qualitative case study research involves 20 pairs of female participants from a public university in Kanazawa, Japan. The data are obtained through video-recorded role-play exchanges based on provided scenarios. The findings reveal that refusals are not expressed as direct rejections but rather emerge through a staged, interactionally negotiated process characterized by indirectness, mitigation, and sensitivity to interpersonal relationships. Speakers collaboratively construct refusals through gradual shifts in speech functions and role relations, often employing incongruent realizations in which linguistic forms diverge from their intended communicative functions. These patterns enable participants to manage face-threatening acts while preserving social harmony. The study underscores the role of discourse-semantic resources and politeness strategies in shaping refusal practices, offering broader implications for cross-cultural communication, pragmatics, and the teaching of Japanese as a foreign language, particularly in developing learners’ awareness of culturally appropriate interactional norms.